Different combinations of formic, propionic and benzoic acids in slaughter offal preservation for feeding to fur animals - Pölönen, Ilpo; Toivonen, Vesa; Mäkelä, Jaakko (Elsevier, 1998)
Abstract Washed rumens, intestines and lungs of beef cattle, were ground, homogenized and acidified with formic acid, 6 g kg-1. The acidified offal was divided into 30 plastic buckets, assigned to two storage temperatures (4°C, 20°C) and 5 treatments with propionic and benzoic acids, (in g kg-1): 0+0, 2+0, 1+1, 0+2 and 3+1. At 4°C, the organoleptic quality of the silages containing additive acids was good for the whole storage time (35 d), while at 20°C all the silages containing 2 g kg-1 additive acids were spoiled. Yeasts predominated the deterioration process with all treatments. Benzoic acid inhibited yeast growth significantly better than formic acid alone, or added propionic acid. Biogenic amines increased only as a result of bacterial growth.
Keywords: Ko; turkiseläimet; rehut; slaughterhouse offal; fur animals; preservation; formic acid; propionic acid; benzoic acid